Liposomal delivery system/adjuvant for tuberculosis vaccine - Melika Moradi; Farzaneh Vahedi; Arian Abbassioun; Arash Ramezanpour Shahi; Mohammad Sholeh; Mortaza Taheri‐Anganeh; Zahra Dargahi; Roya Ghanavati; Seyyed Hossein Khatami; Ahmad Movahedpour (Immunity, Inflammation and Disease)
Abstract As reported by the World Health Organization, about 10 million individuals were infected with tuberculosis (TB) worldwide. Moreover, approximately 1.5 million people died of TB, of which 214,000 were infected with HIV simultaneously. Due to the high infection rate, the need for effective TB vaccination is highly felt. Until now, various methodologies have been proposed for the development of a protein subunit vaccine for TB. These vaccines have shown higher protection than other vaccines, particularly the Bacillus culture vaccine. The delivery system and safety regulator are common characteristics of effective adjuvants in TB vaccines and the clinical trial stage. The present study investigates the current state of TB adjuvant research focusing on the liposomal adjuvant system. Based on our findings, the liposomal system is a safe and efficient adjuvant from nanosize to microsize for vaccinations against TB, other intracellular infections, and malignancies. Clinical studies can provide valuable feedback for developing novel TB adjuvants, which ultimately enhance the impact of adjuvants on next‐generation TB vaccines.